On relativistic models in the equilibrium statistical mechanics - Tretyak, V. (Condensed Matter Physics, 1998)
Relativistic effects in the thermodynamical properties of interacting particle
systems are investigated within the framework of the relativistic direct interaction theory in various forms of dynamics. In the front form of relativistic
dynamics an exactly solvable model of a one-dimensional hard spheres
gas is formulated and an equation of state and thermodynamical potentials
for such a gas are found. Weakly relativistic corrections to the thermodynamical functions of the dilute gas with short-range interactions are discussed on the basis of the approximately relativistic Hamiltonian function
in the instant form of dynamics. Досліджуються релятивістичні ефекти у термодинамічних властивостях систем взаємодіючих частинок у рамах релятивістичної теорії
прямої взаємодії у різних формах динаміки. У фронтальній формі релятивістичної динаміки сформульовано одновимірну модель газу
твердих сфер, що має точний розв’язок; знайдено рівняння стану та
термодинамічні потенціяли. Обговорено слабкорелятивістичні поправки до термодинамічних функцій розрідженого газу з близькосяжними взаємодіями на основі наближеної релятивістичної функції
Гамільтона у миттєвій формі динаміки.